Environmental Catalysis: Present and Future. Issue 1 (29th November 2018) - Rodríguez‐Padrón, Daily; Puente‐Santiago, Alain R.; Balu, Alina M.; Muñoz‐Batista, Mario J.; Luque, Rafael
Abstract: Environmental catalysis plays a crucial role in sustainable development by the design of novel catalytic materials and technologies. Several environmental issues are addressed by catalytic processes such as decomposition of pollutants for air, water and soil remediation, hydrogen production, CO2 reduction and biomass valorization, just to name a few. This contribution aims to provide a general overview of the main concepts and current advances in the environmental catalysis field. Special attention has been paid to photocatalysis and electrocatalysis, as sub‐areas of catalysis with tremendous potential in sustainable applications, in particular with regard to the promotion of sustainable energies. In this contribution, the partnership between Catalysis and Green Chemistry is presented, in a comprehensive way, as an open research line which is imperative and decisive for a more sustainable future. Abstract : Putting the E in Catalysis : Environmental catalysis (bio‐catalysis, electro‐catalysis and photo‐catalysis) are presented, in a comprehensive way, as future research avenues of high potential, imperative for a more sustainable future.